Cancer patient experience measures: An evidence review. Issue 3 (3rd May 2016) - Saunders, Carla; Carter, David J.; Jordan, Amy; Duffield, Christine; Bichel-Findlay, Jen
ABSTRACT: Objectives: This research investigates the instruments currently available to measure the cancer patient experience of health care. An investigation of the number of instruments, the domains covered by the instruments, and the structure and psychometric performance of instruments is undertaken. Methods: A narrative synthesis approach is used to gather evidence from multiple studies and explain the findings. Purposely broad search terms and strategies are used to capture studies with cancer patients at all stages of disease and across a range of cancer types and health care settings. Results: The majority of identified instruments were originally designed for the oncology field. Twelve of the studies developed new cancer patient measures; eight studies adapted existing or utilized items from existing instruments, and seven studies assessed the psychometric properties of existing instruments or assessed validated tools under different conditions (e.g., cross-cultural adaptation). The number of instruments assessing cancer patient experience that have sound psychometric properties across items was found to be low. The properties least tested are test–retest reliability, construct, convergent and discriminant validity, scale variability (floor/ceiling effects), and interpretability. Conclusion: This review examined 10 years of research on the development of instruments to measure the cancer patient experience of health care. It found that research in this area is still in early stages of development. Further inquiry based on development and validation of cancer patient experience measures is required to support improvements in cancer care based on the perspective of cancer patients.